2017
DOI: 10.1139/as-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Permafrost thaw lakes and ponds as habitats for abundant rotifer populations

Abstract: Thermokarst lakes and ponds were sampled across a range of permafrost landscapes in subarctic Québec (Nunavik, Canada) to compare their rotifer and other zooplankton characteristics with a set of rock-basin lakes and ponds in the region. A total of 24 rotifer species were identified, with an average of seven taxa per waterbody. Rotifer abundance was an order of magnitude higher in the thaw ponds than in rock-basin waters. In some thaw ponds, rotifers accounted for >50% of the total zooplankton biomass, but fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 91 publications
3
19
1
Order By: Relevance
“…Due to the fractionation during methanogenesis, methane has more negative δ 13 C values and can be metabolized by methanotrophic bacteria, which then enter the food web (Bastviken et al ). Mixotrophic algae constitute a major fraction of the total phytoplankton community growing in the thaw ponds of the region (Bégin and Vincent ) and could rely on the methanotrophic bacteria as an energy source, explaining the more depleted δ 13 C signature of the phytoplankton. Given the extreme shallowness (< 1 m) and the absence of stratification in bedrock and tundra ponds, the benthic source was an important contributor to DOM, likely resulting from the resuspension of decomposed benthic materials (Evans ) and by diffusion of benthic carbon exudates to the water column (Rautio et al ; Rodríguez et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fractionation during methanogenesis, methane has more negative δ 13 C values and can be metabolized by methanotrophic bacteria, which then enter the food web (Bastviken et al ). Mixotrophic algae constitute a major fraction of the total phytoplankton community growing in the thaw ponds of the region (Bégin and Vincent ) and could rely on the methanotrophic bacteria as an energy source, explaining the more depleted δ 13 C signature of the phytoplankton. Given the extreme shallowness (< 1 m) and the absence of stratification in bedrock and tundra ponds, the benthic source was an important contributor to DOM, likely resulting from the resuspension of decomposed benthic materials (Evans ) and by diffusion of benthic carbon exudates to the water column (Rautio et al ; Rodríguez et al ).…”
Section: Discussionmentioning
confidence: 99%
“…While abiotic factors (DOC, pH, conductivity) accounted for most of the variability in bacterial community structure (Crevecoeur, Vincent, Comte, & Lovejoy, ), they had only limited explanatory power for phytoplankton community structure. These waters are known to host abundant zooplankton populations, including cladocerans and diverse rotifers (Bégin & Vincent, ), and it is likely that these have a strong top down influence on phytoplankton species composition, as observed in other aquatic ecosystems (Hessen & Kaartvedt, ). However, future changes in the physicochemical environment are likely to exceed the natural variability observed here, and could drive shifts in phytoplankton community composition that are not evident from the relatively weak correlative relationships in our taxonomic survey.…”
Section: Discussionmentioning
confidence: 99%
“…planktonicum observed in our experiment is of particular concern for water quality in that many species of Dolichospermum are known to produce neurotoxins (Li, Dreher, & Li, ), and D. planktonicum also produces a microcystin‐like liver toxin (Bruno, Barbini, Pierdominici, Serse, & Ioppolo, ). Extracts of D. planktonicum have strong inhibitory effects on the growth and reproduction of rotifers and cladocerans (Barrios, Nandini, & Sarma, ), two zooplankton groups in the food web of permafrost thaw lakes (Abramova et al., ; Bégin & Vincent, ). The stimulation of picocyanobacteria by P enrichment would likely compound the stresses imposed on the zooplankton, given that subarctic picoplankton appear to be a poor quality food source for cladocerans in these thaw lakes (Przytulska, Bartosiewicz, Rautio, Dufresne, & Vincent, ).…”
Section: Discussionmentioning
confidence: 99%
“…Viruses are intracellular obligate parasites and therefore their dynamics are inextricably linked to those of their hosts. The diversity of Bacteria (Comte et al 2016a,b), Archaea (Crevecoeur et al 2015(Crevecoeur et al , 2016 and protists (Przytulska et al 2016, Bégin & Vincent 2017, the presumptive primary hosts of the subarctic thermokarst viruses, has recently been characterized in several Québec subarctic ponds. Crevecoeur et al (2015) reported that the largest differences in bacterial diversity were between the 2 permafrost landscape types (palsa vs. lithalsa), and Comte et al (2016b) concluded that the composition of these communities appears to be primarily determined by environmental filtering and dispersal limitation.…”
Section: Introductionmentioning
confidence: 99%